PENDEKATAN INDEKS ECKEL DALAM PENGARUH ASIMETRI INFORMASI DAN MANAJEMEN LABA TERHADAP KUALITAS LAPORAN KEUANGAN - Amalia Indah Fitriana; Hendra Galuh Febrianto (Universitas Agung Podomoro, 2019)
One industry sector that plays an important role for the economy in Indonesia is a manufacturing company. Because manufacturing companies are a big contributor to income for the country through taxes and other contracts. Because manufacturing companies have large asset values, they will face several business risks such as making earnings management. Companies with earnings management can result in a collapse of the company.The purpose of this study is to be able to analyze the impact of the effect between earnings management and information asymmetry in manufacturing companies listed on the Indonesia Stock Exchange (IDX), with the ultimate goal of recommending policies to improve manufacturing management. In this study the type of research is explanatory research using a quantitative approach. The data analysis in this study uses multiple linear regression analysis and path analysis (Path analysis) on the financial statements of 300 manufacturing companies from 2013 to 2017.In this study the results for manufacturing companies listed on the Stock Exchange for the period 2013-2017 the results are as follows: H1 testing shows that the earnings management with information asymmetry has a significant effect. H2 testing can conclude the results that the quality of financial statements on earnings management and information asymmetry does not have a significant effect.